THE INFLUENCE OF GEOLOGICAL AND GEOMORPHOLOGICAL FACTORS ON THE CREATION OF A NETWORK OF FOUR LAKES IN THE TALAS VALLEY. (Journal of history, 2023)
In the article " Influence of geological and geomorphological factors on the creation of a network of tortkols in the Talas Valley", the aim of the work is to clarify the geological and geomorphological conditions in the Talas River basin that contributed to the selection of sites for the construction of tortcoles - outposts of the Middle Ages. Geological and geomorphological analysis of the locations of the tortcoles allowed us to identify the patterns of their localization. So, along with the main riverbed, the branches, channels and dry valleys of a large area of the Pritalasye were of great importance. The following conditions favored the emergence of a dense network of tortkols: strategic location, availability of water sources and raw materials for housing construction, water availability of adjacent territories. All these factors directly depended on the geological and structural features and relief of this territory. This study allows us to identify patterns in the choice of the main routes of movement of caravans and the localization of points that perform a security function.Key words: Talas valley; Shu-Talas trough; medieval torkoli; alluvial plain; Late Anthropogenic alluvial fan; floodplain; terraces; anticlines; kersh; loams; rocks of the Andasai Formation